A Review on the Thermal Insulation Potential of Traditional Kashmiri Construction Materials for Energy-Efficient Housing - Shaista Zainab; Preetpal Singh (PT. Radja Intercontinental Publishing, 2025)
Energy efficiency in buildings is a crucial aspect of sustainable architecture, particularly in cold climatic regions like Kashmir. Traditional Kashmiri construction materials have been utilized for centuries, yet their thermal insulation properties lack comprehensive scientific validation. This review paper critically examines existing research on indigenous Kashmiri building materials, highlighting the research gap in experimental quantification of their insulation properties. The paper discusses the thermal performance of materials such as Compressed Earth Blocks (CEB), Timber, Willow Mats, Mud Plaster, and Stone Masonry, emphasizing their potential for modern energy-efficient housing. A comparative analysis with contemporary insulation materials is conducted, and hybrid insulation strategies are proposed to optimize energy conservation. The review underscores the necessity for policy interventions to promote the adoption of vernacular materials and advocates for further studies focusing on real-time thermal performance assessments, lifecycle cost analyses, and integration with modern construction technologies.